2021
DOI: 10.1016/j.apmr.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal White Matter Abnormalities Associated With Pain Catastrophizing in Patients With Complex Regional Pain Syndrome

Abstract: To investigate altered prefrontal white matter integrity in complex regional pain syndrome (CRPS) and its relation with the degree of pain catastrophizing. Design: Cross-sectional study. Setting: University hospital. Participants: Twenty-one CRPS patients and 49 patients without CRPS (NZ70). Interventions: Not applicable. Main Outcome Measures: The fractional anisotropy values within the prefrontal regions reflecting the structural integrity of white matter were measured in CRPS patients and patients without C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…The corpus callosum is a major WM throughfare connecting the hemispheres of the brain. DTI has typically shown decreased FA in various parts of the CC with chronic pain, which varied by study ( Buckalew et al, 2010 , Geha et al, 2008 , Im et al, 2021 , Kim et al, 2014 , Li et al, 2021b , Moayedi et al, 2012 ); in migraine, by contrast, multiple studies found lower FA in all regions of CC ( Li et al, 2011 , Yu et al, 2013 ). Some of these FA changes have been correlated with clinical measures: decreased FA in the CC body of fibromyalgia patients ( Kim et al, 2014 ) and the genu of trigeminal neuralgia patients ( Li et al, 2021b ) were both negatively associated with pain intensity, mirroring our results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corpus callosum is a major WM throughfare connecting the hemispheres of the brain. DTI has typically shown decreased FA in various parts of the CC with chronic pain, which varied by study ( Buckalew et al, 2010 , Geha et al, 2008 , Im et al, 2021 , Kim et al, 2014 , Li et al, 2021b , Moayedi et al, 2012 ); in migraine, by contrast, multiple studies found lower FA in all regions of CC ( Li et al, 2011 , Yu et al, 2013 ). Some of these FA changes have been correlated with clinical measures: decreased FA in the CC body of fibromyalgia patients ( Kim et al, 2014 ) and the genu of trigeminal neuralgia patients ( Li et al, 2021b ) were both negatively associated with pain intensity, mirroring our results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between WM microstructure and pain catastrophizing has seldom been investigated, though one recent DTI study in complex regional pain syndrome (CRPS) found weakening in the PFC of patients versus controls, which in turn correlated with pain catastrophizing ( Im et al, 2021 ). Functional studies, meanwhile, have found that connectivity between medial PFC or PCC and the rest of the DMN were related to pain catastrophizing and rumination ( Kucyi et al, 2014 , Lee et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These psychological stress responses lead to increased catecholamine secretion, a lower threshold for noxious stimuli, and sympathetic nerve overdrive. Pain catastrophizing affects CRPS development profoundly ( 36 ), and patients with such psychological tendencies have persistently higher pain scores ( 37 ).…”
Section: Clinical Summary Of Crpsmentioning
confidence: 99%
“…Furthermore, a reduced activation of cortical areas during the motor imagery (MI) task in the affected side 15 has been observed, and changes in motor areas such as the premotor cortex that is involved in MI abilities 7,16,17 .…”
Section: Introductionmentioning
confidence: 99%